Strategi Efektif dalam Meningkatkan Minat Belajar Siswa Sekolah Dasar - Herlinda Restiani (JPT : Jurnal Pendidikan Tematik, 2024)
This study aims to identify effective strategies that can improve elementary school students' interest in learning. High interest in learning is an important factor in achieving academic success, especially at the elementary level. In this context, it is important to find methods that can motivate students and make the learning process more interesting and enjoyable. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with teachers and students, direct observations in the classroom, and document analysis related to the teaching methods applied. The results of the study indicate that the implementation of active learning strategies, such as project-based learning, the use of interactive technology, and educational games, is very effective in improving students' interest in learning. In addition, teachers who are able to build good relationships with students and create a positive learning environment also have an important role in improving student motivation. This study also found that parental participation in the learning process at home can strengthen students' interest in learning. Therefore, collaboration between teachers, students, and parents is very necessary to create an optimal learning atmosphere. These findings are expected to provide guidance for teachers and education stakeholders in designing effective strategies to improve students' interest in learning in elementary schools.